(NEt(4))(2)[Fe(CN)(2)(CO)('S(3)')]: an iron thiolate complex modeling the [Fe(CN)(2)(CO)(S-Cys)(2)] site of [NiFe] hydrogenase centers. - Sellmann, Dieter; Geipel, Franz; Heinemann, Frank Wilhelm (Chemistry - A European Journal, 2002)
In the search for complexes modeling the [Fe(CN)(2)(CO)(cysteinate)(2)] cores of the active centers of [NiFe] hydrogenases, the complex (NEt(4))(2)[Fe(CN)(2)(CO)('S(3)')] (4) was found ('S(3)'(2-)=bis(2-mercaptophenyl)sulfide(2-)). Starting complex for the synthesis of 4 was [Fe(CO)(2)('S(3)')](2) (1). Complex 1 formed from [Fe(CO)(3)(PhCH=CHCOMe)] and neutral 'S(3)'-H(2). Reactions of 1 with PCy(3) or DPPE (1,2-bis(diphenylphosphino)ethane) yielded diastereoselectively [Fe(CO)(2)(PCy(3))('S(3)')] (2) and [Fe(CO)(dppe)('S(3)')] (3). The diastereoselective formation of 2 and 3 is rationalized by the trans influence of the 'S(3)'(2-) thiolate and thioether S atoms which act as pi donors and pi acceptors, respectively. The trans influence of the 'S(3)'(2-) sulfur donors also rationalizes the diastereoselective formation of the C(1) symmetrical anion of 4, when 1 is treated with four equivalents of NEt(4)CN. The molecular structures of 1, 3 x 0.5 C(7)H(8), and (AsPh(4))(2)[Fe(CN)(2)(CO)('S(3)')] x acetone (4 a x C(3)H(6)O) were determined by X-ray structure analyses. Complex 4 is the first complex that models the unusual 2:1 cyano/carbonyl and dithiolate coordination of the [NiFe] hydrogenase iron site. Complex 4 can be reversibly oxidized electrochemically; chemical oxidation of 4 by [Fe(Cp)(2)PF(6)], however, led to loss of the CO ligand and yielded only products, which could not be characterized. When dissolved in solvents of increasing proton activity (from CH(3)CN to buffered H(2)O), complex 4 exhibits drastic nu(CO) blue shifts of up to 44 cm(-1), and relatively small nu(CN) red shifts of approximately 10 cm(-1). The nu(CO) frequency of 4 in H(2)O (1973 cm(-1)) is higher than that of any hydrogenase state (1952 cm(-1)). In addition, the nu(CO) frequency shift of 4 in various solvents is larger than that of [NiFe] hydrogenase in its most reduced or oxidized state. These results demonstrate that complexes modeling properly the nu(CO) frequencies of [NiFe] hydrogenase probably need a [Ni(thiolate)(2)] unit. The results also demonstrate that the nu(CO) frequency of [Fe(CN)(2)(CO)(thiolate)(2)] complexes is more significantly shifted by changing the solvent than the nu(CO) frequency of [NiFe] hydrogenases by coupled-proton and electron-transfer reactions. The "iron-wheel" complex [Fe(6)[Fe('S(3)')(2)](6)] (6) resulting as a minor by-product from the recrystallization of 2 in boiling toluene could be characterized by X-ray structure analysis.